The development and codesign of the PATHway intervention: a theory-driven eHealth platform for the self-management of cardiovascular disease. Issue 1 (15th March 2018) - Walsh, Deirdre M J; Moran, Kieran; Cornelissen, Veronique; Buys, Roselien; Claes, Jomme; Zampognaro, Paolo; Melillo, Fabio; Maglaveras, Nicos; Chouvarda, Ioanna; Triantafyllidis, Andreas; Filos, Dimitris; Woods, Catherine B
Abstract : The development of technology-based interventions for people with cardiovascular disease needs to be reported clearly throughout each development stage. This kind of reporting will allow future research to repeat best practice development and can aid future evaluation. Abstract: Cardiovascular diseases (CVDs) are a leading cause of premature death worldwide. International guidelines recommend routine delivery of all phases of cardiac rehabilitation (CR). Uptake of traditional CR remains suboptimal, as attendance at formal hospital-based CR programs is low, with community-based CR rates and individual long-term exercise maintenance even lower. Home-based CR programs have been shown to be equally effective in clinical and health-related quality of life outcomes and yet are not readily available. The aim of the current study was to develop the PATHway intervention (physical activity toward health) for the self-management of CVD. Increasing physical activity in individuals with CVD was the primary behavior. The PATHway intervention was theoretically informed by the behavior change wheel and social cognitive theory. All relevant intervention functions, behavior change techniques, and policy categories were identified and translated into intervention content. Furthermore, a person-centered approach was adopted involving an iterative codesign process and extensive user testing. Education, enablement, modeling, persuasion, training, and social restructuring were selected as appropriate intervention functions. Twenty-two behavior change techniques, linked to the six intervention functions and three policy categories, were identified for inclusion and translated into PATHway intervention content. This paper details the use of the behavior change wheel and social cognitive theory to develop an eHealth intervention for the self-management of CVD. The systematic and transparent development of the PATHway intervention will facilitate the evaluation of intervention effectiveness and future replication.